The non-incidence of income tax on alimony or child support (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2024)
The article discusses the STF decision in ADI No. 5.422/DF, which determined the non-incidence of income tax on alimony. It examines the impact of this taxation on the existential minimum, human dignity, and gender inequality, as its incidence harms the subsistence of the recipient.Received in: August 2024 | Accepted in: September 2024
Keywords: Alimony; Child support; Income Tax